2013
DOI: 10.4137/nmi.s12584
|View full text |Cite
|
Sign up to set email alerts
|

High D(+)-Fructose Diet Adversely Affects Testicular Weight Gain in Weaning Rats—Protection by Moderate D(+)-Glucose Diet

Abstract: The use of high D(+)-fructose corn syrup has increased over the past several decades in the developed countries, while overweight and obesity rates and the related diseases have risen dramatically. However, we found that feeding a high D(+)-fructose diet (80% D(+)-fructose as part of the diet) to weaning rats for 21 days led to reduced food intake (50% less, P < 0.0001) and thus delayed the weight gains in the body (40% less, P < 0.0001) and testes (40% less, P < 0.0001) compared to the no D(+)-fructose diet. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
2
5
0
Order By: Relevance
“…Other findings in the study supported this hypothesis. The findings in testes weights in our study are similar to ones in previous studies (Shibata & Fukuwatari, ). A decreased testes weight indicates impaired maturation of germ cells (Uygur et al, ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Other findings in the study supported this hypothesis. The findings in testes weights in our study are similar to ones in previous studies (Shibata & Fukuwatari, ). A decreased testes weight indicates impaired maturation of germ cells (Uygur et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…Testis is the most sensitive organ, and high‐fructose intake reduces testicular weight. Thus, high‐fructose diets can cause infertility (Shibata & Fukuwatari, ).…”
Section: Introductionmentioning
confidence: 99%
“…Possibly altered glucose metabolism due to fructose-feeding might have impaired the testis development at early stages. In support to our observation, a recently published short report during our experiment reported a significant decrease in testis weight in weaning Wistar rats which were fed with 70–80% fructose diets and the authors also reported that glucose supplementation restored the weight of testis [48]. …”
Section: Discussionsupporting
confidence: 90%
“…Intake of 70% fructose, but not glucose, negatively affects weight gain in Wistar rats fed the same amount of protein 22 ; however, weight gain in female rats fed a solution of 13% HFCS ad libitum for 8 weeks has also been reported 20 . HFCS may have little effect on females at the 30 th week of life but still favor significant weight gain in males (8% HFCS) 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Weight changes are not explained solely by protein intake; total glucose intake can also affect weight gain. The amount of glucose in the diet of animals consuming fructose should not be less than 23% of total energy intake 22 . In our study, the glucose proportions in the control and HFr diets were 36 and 37%, respectively, thus same glucose intake could explain the equal weight gain of the animals.…”
Section: Discussionmentioning
confidence: 99%